Kontradiksi Agama dalam Perspektif Hasipelebeguan Tradisi Mangokal Holi Etnis Batak Toba - Pratiwi, Eka Bella; Harahap, Fazira Ismaillia; Br Siallagan, Putri Sion; Tambunan, Riskida Pitamaro; Siregar, Siti Fadilah Aini (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The "Mangokal Holi" tradition in Toba Batak society is a ritual carried out by wealthy or well-to-do individuals to honor ancestors and mark someone as civilized. From the perspective of the Toba Batak people, this tradition is considered respect for ancestors and not worship. This research uses qualitative methods which according to Saroso (2017:47) in ( (Yusra, Zulkarnai & Sofino, 2021) Interviews are one of the techniques most widely used to collect qualitative research data. The results of the research show that the "Mangokal Holi" tradition is a practice Culture is important for the Toba Batak people, especially respecting ancestors and showing obedience to customs and not worship.